Intrahepatic Expression of C-C Motif ligand 5 in Patients with Chronic Hepatitis B - Zhao, Xiang-An; Wang, Jian; Chang, Haiyan; Liu, Yong; Chen, Yuxin; Chen, Guangmei; Huang, Rui; Wu, Chao (Turkish Journal of Gastroenterology, 2021)
Background/Aims: C-C motif ligand 5 (CCL5) is reported to play a key role in acute and chronic liver diseases. However, the association between the CCL5 and chronic hepatitis B (CHB) remains to be explored. We aimed to investigate the CCL5 expression in the liver tissues of CHB patients and compared the CCL5 expression among CHB patients with different stages of liver inflammation and fibrosis.Materials and Methods: Liver tissue specimens from fifty-one CHB patients who underwent liver biopsy and twelve healthy liver donors were included in the present study. CCL5 expression in the liver tissues was analyzed using immunohistochemistry. The hepatic inflammation grades and fibrotic stages of CHB patients was assessed by the Scheuer classification system.Results: Livers of CHB patients exhibited a significantly accumulated CCL5+ cells when compared to that of healthy controls (42.80±4.37 vs 7.25±0.99/HPF, p<0.001). CHB patients with higher hepatic inflammation grades had more CCL5+ cells in their livers compared to those with lower grades (p<0.05). However, the numbers of CCL5+ cells were not correlated with the fibrotic stages in CHB patients (r=0.073, p=0.61). The number of CCL5+ cells in the liver tissues of CHB patients were positively correlated with alanine transaminase levels (r=0.278, p=0.041) and aspartate aminotransferase levels (r=0.328, p= 0.009).Conclusion: CHB patients have a significant accumulation of CCL5+ cells in the liver, and CCL5 may play a pathological role in hepatic inflammation of CHB.